DIGITAL CITIZENSHIP: FORMING TECHNOLOGY ETHICS IN ELEMENTARY SCHOOL CHILDREN - Fajar Dwi Mukti (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2023)
This research aims to investigate the impact of digital technology development on the education of primary school children, focusing on the formation of technological ethics. In this context, the study identifies key issues such as children's lack of understanding of the negative consequences of technology use and the potential loss of control over usage time. The research methodology employed is a literature review, analyzing findings related to technological ethics among primary school children. The results indicate that despite most children having access to digital devices, their understanding of technical ethics is limited. This includes a low awareness of online privacy, data protection, and communication ethics. The implications of the research underscore the urgency of digital education and the crucial roles of parents and schools in guiding children toward responsible and ethical use of technology. These findings provide a foundation for future collaborative efforts in shaping accountable and honest digital citizens.